Pengaruh Umpan Balik Dalam Asesmen Formatif Terhadap Peningkatan Hasil Belajar Siswa Dalam Kurikulum Merdeka - Anita Candra Dewi (Prodi PGSD Unsultra, 2024)
This study aims to analyze the effect of feedback in formative assessment on improving student learning outcomes in private junior high schools in Makassar City. The research method used is a quasi-experimental design with a pretest-posttest control group design. The sample consisted of 80 eighth grade students who were divided into two groups: the experimental group (40 students) who received in-depth formative feedback and the control group (40 students) who only received minimal feedback. Data were collected through learning outcome tests (pretest and posttest), classroom observations, and student perception questionnaires. Data analysis was carried out using a t-test to measure differences in learning outcomes between the two groups. The results showed that the experimental group experienced an increase in scores of 17.3 points, while the control group only increased by 7.5 points. More specific and reflective formative feedback contributed significantly to improving student learning outcomes.